Apple NAC transcription factor MdNAC52 regulates biosynthesis of anthocyanin and proanthocyanidin through MdMYB9 and MdMYB11. (December 2019) - Sun, Qingguo; Jiang, Shenghui; Zhang, Tianliang; Xu, Haifeng; Fang, Hongcheng; Zhang, Jing; Su, Mengyu; Wang, Yicheng; Zhang, Zongying; Wang, Nan; Chen, Xuesen
Highlights: An apple NAC protein, MdNAC52, is involved in regulating the flavonoid pathway. MdHY5 targets MdNAC52 to regulate anthocyanin accumulation. MdNAC52 promotes proanthocyanidin accumulation via MdMYB9 and MdMYB11. MdNAC52 binds to the promoter of MdLAR in the proanthocyanidin pathway. Abstract: Anthocyanin and proanthocyanidin (PA) play important roles in plant growth and development. Although previous studies have identified many of the transcription factors involved in the anthocyanin and PA pathway, the regulation mechanisms of these pathways remain poorly understood. In this study, we identified a NAC transcription factor, MdNAC52, whose gene transcript levels increased during apple coloration. Apple calli overexpressing MdNAC52 accumulated anthocyanin. Yeast one-hybrid, electrophoretic mobility shift, chromatin immunoprecipitation, and luciferase reporter assays showed that MdNAC52 could interact with the promoters of MdMYB9 and MdMYB11 to regulate anthocyanin biosynthesis. MdNAC52 was targeted by MdHY5 in response to light. Interestingly, MdNAC52 participated in the regulation of PA biosynthesis through controlling the expression of MdMYB9 and MdMYB11 . MdNAC52 could also bind to the LAR promoter to regulate its expression and promote PA synthesis. Overall, these findings establish that MdNAC52 binds to the promoters of MdMYB9 and MdMYB11 to promote anthocyanin and PA biosynthesis and directly regulates LAR to modulate PA metabolism. Our study provides new insights into the roles of a NAC transcription factor in regulating anthocyanin and PA accumulation in apple.